'In a twilight world'? Judging the value of life for the minimally conscious patient. Issue 9 (12th October 2012) - Huxtable, Richard
Abstract : The recent ruling from England on the case of M is one of very few worldwide to consider whether life-sustaining treatment, in the form of clinically assisted nutrition and hydration, should continue to be provided to a patient in a minimally conscious state. Formally concerned with the English law pertaining to precedent autonomy (specifically advance decision-making) and the best interests of the incapacitated patient, the judgment issued in M's case implicitly engages with three different accounts of the value of human life, which respectively emphasise its self-determined, intrinsic and instrumental value. The judge appeared to be most persuaded by the intrinsic value of life and he concluded that treatment ought to continue. Assessing whether his approach or conclusion were ethically appropriate involves significant substantive and evidential questions regarding where the burden of proof should lie and what standard of proof should be required when decisions are to be made about the fates of patients inhabiting 'twilight worlds'.